1996
DOI: 10.1007/bf00222957
|View full text |Cite
|
Sign up to set email alerts
|

A phylogenetic analysis of Pisum based on morphological characters, and allozyme and RAPD markers

Abstract: Cladistic analyses of 17 wild and cultivated pea taxa were performed using morphological characters, and allozyme and RAPD (random amplified polymorphic DNA) markers. Both branch-and-bound and bootstrap searches produced cladograms that confirmed the close relationships among the wild species and cultivars of Pisum proposed by a variety of systematic studies. Intraspecific rankings were supported for northern P. humile, southern P. humile, P. elatius and P. sativum, which together comprise a single-species com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
32
0
2

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(40 citation statements)
references
References 18 publications
6
32
0
2
Order By: Relevance
“…Within groups, known genealogies often supported the aggregations. This classification is in agreement with other studies: Hoey et al (1996) using allozymes and RAPDs and Ellis et al (1998) using Ty1-copia retrotransposon-derived SSAP markers have also shown a clear distinction between wild ecotypes and cultivated peas. Within wild ecotypes, in our study as well as in those of Ellis et al (1998) and Lu et al (1996), accessions from Caucasus formed a distinct group, and P. humile JI241 clustered with accessions originating from Afghanistan.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Within groups, known genealogies often supported the aggregations. This classification is in agreement with other studies: Hoey et al (1996) using allozymes and RAPDs and Ellis et al (1998) using Ty1-copia retrotransposon-derived SSAP markers have also shown a clear distinction between wild ecotypes and cultivated peas. Within wild ecotypes, in our study as well as in those of Ellis et al (1998) and Lu et al (1996), accessions from Caucasus formed a distinct group, and P. humile JI241 clustered with accessions originating from Afghanistan.…”
Section: Discussionsupporting
confidence: 92%
“…Recent diversity studies in pea have focused either on biosystematic studies within the Pisum genus (Hoey et al 1996;Ellis et al 1998), or on the assessment of different molecular markers to investigate the genetic diversity within Pisum (Lu et al 1996;Posvec and Griga 2000;Burstin et al 2001;Simioniuc et al 2002). However, all these studies have focused either on rather small numbers of accessions, or on specific groups of pea genotypes.…”
Section: Communicated By C Möllersmentioning
confidence: 98%
“…The position of different groups within P. sativum varied. For example, a reconstruction based on morphological, allozyme and RAPD markers (Hoey et al, 1996) was consistent with karyologic studies of the same lines (BenZe'ev and Zohary, 1973). On the phylogenetic trees obtained by Ellis et al (1998) and Jing et al (2007), topology of branches leading to accessions attributed to 'P.…”
Section: Introductionmentioning
confidence: 74%
“…Several attempts were made recently to reconstruct phylogenetic relationships among peas (Ellis et al, 1998;Hoey et al, 1996;Jing et al, 2007Jing et al, , 2010Lu et al, 1996;Vershinin et al, 2003). All of them resulted in P. fulvum and P. abyssinicum to form separate branches on the trees, but the branch of P. fulvum was basic while that of P. abyssinicum resided within P. sativum, making the latter a paraphyletic species.…”
Section: Introductionmentioning
confidence: 99%
“…With the advent of polymerase chain reaction (PCR) technique, two quick and simple methods called random amplified polymorphic DNA, RAPD (Williams et al 1990) and inter-simple sequence repeat, ISSR (Zietkiewicz et al 1994) are now widely used for the study of phylogeny and genetic diversity. RAPD markers have been used for the identification of cultivars and for assessing genetic diversity among cultivars of several crops like bean (Skroch et al 1992), pea (Hoey et al 1996), soybean (Brown-Guedira et al 2000), Ceratotropis (Kaga et al 1996), mungbean (Santalla et al 1998, Lakhanpaul et al 2003, etc. ISSRs are semiarbitrary markers amplified by PCR in the presence of one primer complementary to a target microsatellite.…”
Section: ⎯⎯⎯⎯mentioning
confidence: 99%